English legal system (Routledge-Cavendish, 2008)
Routledge-Cavendish Lawcards are complete, pocket-sized guides to key examinable areas of the undergraduate law curriculum and the CPE/GDL. Their concise text, user-friendly layout and compact format make them an ideal revision aid for identifying, understanding and committing to memory the salient points of each area of the law.